Nicaraguans in Costa Rica and the United States: data from Ethnic Surveys (Translation of Spanish Version) - Vargas Aguilar, Juan Carlos (2005)
In Central America, Nicaragua is the only country with a clearly bipolar behavior regarding the destination of its emigration streams. Emigration from Nicaragua has Costa Rica as its major destination and the United States in second place. This behavior has not been static, insofar as it also shows the opposite pattern. From mid-19th Century through the end of the 70’s, with the Sandinista triumph (1979), Costa Rica was the main destination. During the 80’s, and the so-called Contra War, there was an increase in emigration and the destination changed, with the United States occupying first place. Once the armed conflict ceased, and the Sandinistas were voted out of office, Costa Rica again assumed the role of primary destination, and this time with a growth in the flow with regards to historic behavior (Vargas; 1999, 2003).In spite of the size of this migration stream and the repercussions for Costa Rica, there have been few studies aimed at analyzing it systematically. One important effort was implemented by Jimmy Rosales et al, in their study of the “nicaragüenses en el exterior” (Nicaraguans abroad) (Rosales: 2001), with data from the Nicaraguan Census of 1995. Other time-limited studies with fieldwork have been carried out in some border communities with Costa Rica by FLACSO-Costa Rica researchers (Morales; 1997, 2000) (Morales and Castro, 2002).Recently, using data from ethnosurveys (for 5 communities in Nicaragua and other countries), several studies have been prepared on specific topics. Fussell (2003) has reviewed the evidence for the theory of cumulative causation provided by this migration; Riosmena (2003) has studied the possibilities of return, and Hickes and Massey (2003), have studied the relations with armed conflict and political conflict in Nicaragua and migrant destination. This paper analyzes the basic demographic characteristics of the migrants, as well as the migration streams with a comparative look at destinations. We are looking for evidence of the so-called “labor migration” to Costa Rica and the “political migration” to the United States and to contribute to a discussion on the adequateness of this distinction. Among other things, we analyze the prevalence rates and the differential characteristics of migrants between the two destination countries. Migrant data is related to community of origin together with some of the evidence on the impactmigration has on these communities.